PAIDEIA ADAPTATION: CAN WE TRANSFORM PEDAGOGICAL MATERIALS INTO ANTHROPOMORPHIC NARRATIVES? - Pujiyanti, Umi; Muhammad Rizal; Robith Khoiril Umam (UIN Raden Mas Said Surakarta, 2023)
Paideia philosophy urges education and anything derived or related to it to respond to the zeitgeist of an era. Thus, techniques to deliver any pedagogical materials should position the target users as the axis to disclose them more possibilities to comprehend the materials. One of the techniques is designing anthropomorphic narratives. Studies on this topic circumnavigate around educational domains. Perceiving this issue from the lens of literary adaptation is the gap left by the previous studies. We argue that narrating pedagogical materials anthropomorphically is better termed paideia adaptation. This study attempts to prove the existence of this adaptation type by utilizing qualitative method, indicating the narrative and language features of the adaptation. Implementing the theories of onto fiction by Couceiro-Bueno, ergodic literature by Aarseth, second degree of literature by Genette, anthropomorphism by Weemans and Prévost on a corpus of animated films and games, the findings indicate that paideia adaptation has four narrative features namely anthropomorphic narratives, pseudoreferentiality, metalepsis, and metafictionality. This adaptation also has distinctive language features namely thematization, proairetic decoding, and didacticization. The result discloses a new viewpoint in the study of adaptation.